Three new species of Aspergillus section Flavi isolated from almonds and maize in Portugal - Soares, Célia (2012)
Three new aflatoxin-producing species belonging to Aspergillus section Flavi are described, Aspergillus mottae, Aspergillus sergii and Aspergillus transmontanensis. These species were isolated from two Portuguese commodities, almonds and maize. A polyphasic approach based on phenotypic (morphology and extrolites) and molecular characterizations was used to identify these isolates as belonging to new species. Molecular characterization showed that A. transmontanensis and A. sergii are phylogenetically related to Aspergillus parasiticus whereas A. mottae is phylogenetically ancestral to Aspergillus flavus and A. parasiticus.